Efektivitas Peran Modin Dalam Mencegah Pernikahan Usia Dini Di Kecamatan Puger Kabupaten Jember - Mohammad Ardhi Wildan; Moh. Ali Syaifudin Zuhri (State Islamic University of Kiai Haji Achmad Siddiq Jember, 2023)
Abstract: In wedding administration, the Puger District Religious Affairs Office is assisted by a Modin in each village to complete the documents needed for marriage. When there is a prospective bride and groom who is less than 19 years old, a Modin provides an explanation, direction and insight that this is considered an early marriage. This is done so that people think twice about getting married at an early age. Therefore, the research conducted by researchers discusses